The final-over-final condition a syntactic universal - Sheehan, Michelle; Biberauer, Theresa; Roberts, Ian G. 1957-; Holmberg, Anders 1951- (The MIT Press, 2017)
This book presents evidence for a universal word order constraint, the Final-Over-Final Condition (FOFC), and discusses the theoretical implications of this phenomenon. FOFC is a syntactic condition that disallows structures where a head-initial phrase is contained in a head-final phrase in the same extended projection/domain. The authors argue that FOFC is a linguistic universal, not just a strong tendency, and not a constraint on processing. They discuss the effects of the universal in various domains, including the noun phrase, the adjective phrase, the verb phrase, and the clause. The book draws on data from a wide range of languages including Hindi, Turkish, Basque, Finnish, Afrikaans, German, Hungarian, French, English, Italian, Romanian, Arabic, Hebrew, Mandarin, Pontic Greek, Bagirmi, Dholuo, and Thai. FOFC, the authors argue, is important because it is the only known example of a word order asymmetry pertaining to the order of heads. As such, it has significant repercussions for theories connecting the narrow syntax to linear order. Book jacket
Keywords: Head-driven phrase structure grammar; Sprachliche Universalien; Wortstellung; Kontrastive Syntax; Grammar, Comparative and general / Syntax; Grammar, Comparative and general / Word order; Aufsatzsammlung